Hope for the embattled language classroom : pedagogies for well-being and trauma healing - Kanna, Olivia (Emerald Publishing Limited : Information Age Publishing Inc., 2022)
"Learning, as it is being increasingly recognized, is centrally predicated upon students' wellbeing. Research findings indicate that in the instances of wounding and trauma, students' capacity and ability to learn can be severely compromised. This understanding applies particularly to the immigrant students in the language classroom, many of whom are refugees bringing with them past experiences of privation, violence, wounding and trauma. Since teachers often find themselves wearing multiple hats, not only as instructors, but also as friends, philosophers, guides, confidantes, and counsellors to their refugee and immigrant learners, addressing those students' trauma with compassion, and employing appropriate pedagogical practices to mitigate their suffering should be of great relevance and inform the teachers' praxis in the classroom. This book takes an interdisciplinary look at trauma from the vantage points of critical language theories, neuroscience, psychotherapy, and Buddhist psychology, and suggests pedagogies for well-being and trauma healing that utilize contemplative ways of education. The practical aim of this book is to support teachers in addressing trauma in their classrooms. Considering the current global transmigrations and refugee relocations that reflect the times we live in, an understanding of trauma and how it affects the ability to learn and consequently impacts employment, resettlement, and acculturation of traumatized populations becomes vital and is the need of the hour. This book provides that much-needed understanding, and government policy planners, international workers dealing with refugees, community refugee and immigrant service organizations, teacher educators and student teachers, language instructors in programs such as Teaching English to Speakers of Other Languages (TESOL), Teaching English as an Additional Language (TEAL), Teaching English as a Second Language (TESL), and Teaching English as a Foreign Language (TEFL), K-12 teachers in public and private schools, contemplative practitioners, educational researchers in trauma studies and related pedagogies, mental health and educational counsellors in school districts, as well as in adult education settings, and practically everyone who believes in the teaching-learning relationship and the role of holistic methods in education for well-being and trauma healing can all benefit from this book. The comprehensive overview of trauma and pedagogies for healing that the book offers makes its appeal both academic and popular. Given the ever-increasing interest these days in ethics in practice, it looks at the philosophical orientations of language teaching through the prism of contemplative inquiry, bolstered by an in-depth understanding of trauma through interdisciplinary approaches. It also answers profound questions that teachers have, such as: Can a greater emphasis on pedagogies and trauma interventions change education for the better, or is one being presumptuous about it? What theory and research data do we have to support such educational initiatives? Would it be ethical to expect teachers, who are already overworked, to become healers in the classroom? Would it be possible for teachers to bring about healing in their traumatized learners? While we would not expect teachers to become therapists, is it possible to create pedagogical approaches that are themselves therapeutic? The book thus makes a powerful case for the absolute and essential need for trauma education to be made a part of teacher education, and will, no doubt, enable all teachers to become trauma-informed professionals who can bring about a transformation in education for the future"-- Provided by publisher.
Keywords: English language -- Study and teaching -- Foreign speakers -- Social aspects.; Immigrant children -- Education.; Refugee children -- Education.; Psychic trauma in children.; Trauma-informed pedagogy.; Education -- Bilingual Education.; Education of bilingual or multilingual students.; elektronické knihy; electronic books